Technological aspects of xanthan gum and gum Arabic presence in chicken egg albumin wet foams: Application of nonlinear rheology and nonparametric statistics. (August 2021) - Kruk, Joanna; Ptaszek, Paweł; Kaczmarczyk, Kacper
Abstract: This study presents the results of physicochemical and rheological studies of wet foams obtained using the batch method, from chicken egg albumin with the addition of xanthan gum and/or gum Arabic. The physicochemical analysis included determination of foam density, volume fraction of gas phase, overrun, stability and the distribution of gas bubbles suspended in liquid. The study on hydrocolloids effect on the distribution of gas bubbles was based on the standard descriptive parameters estimation and the use of nonparametric Kolmogorov–Smirnov test. The results indicated that foams containing only the gum Arabic addition proved to be bimodal, which was demonstrated by the logarithmic scale. In contrast, the addition of xanthan gum didn't change character of gas bubbles distribution. Nonlinear rheological tests were carried out using the LAOS methodology and the results were analysed with the help of geometric decomposition in combination with Chebyshev harmonics analysis. It allowed to identify xanthan gum as a polysaccharide responsible for viscous nature of foam while gum Arabic as a component increasing plasticity. Graphical abstract: Image 1 Highlights: The bimodal character of gas bubbles distributions was demonstrated in wet foams based on chicken egg albumin. Gum Arabic didn't influence on the surface tension but increased overrun values and decreased the values of Sauter diameter. Nonparametric statistical methods were good tool to analysis foams properties. The nonlinear effect of xanthang gum on wet foams' yield stress was demonstrated. The increasing concentration of xanthan gum decreased overrun values but enhanced the rheological stability of wet foams.